2023
DOI: 10.5194/acp-2022-806
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Production of aerosol containing ice nucleating particles (INPs) by fast growing phytoplankton

Abstract: Abstract. Sea spray aerosol contains ice nucleating particles (INPs), which affect the formation and properties of clouds. Here, we show that aerosols emitted from fast growing marine phytoplankton produce effective immersion INPs, which nucleate at temperatures significantly warmer than the atmospheric homogeneous freezing (−38.0 ∘C) of pure water. Aerosol sampled over phytoplankton cultures grown in a marine aerosol reference tank (MART) induced nucleation and freezing at temperatures as high as −15.0 ∘C dur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…For example, Wilson et al (2015) found that the biogenic organic materials within the sea surface microlayer could induce droplet freezing in the immersion mode, with a broad freezing-temperature range of −7.0 to −35.0 °C. Laboratory experiments have further revealed that aerosols generated by phytoplankton are particularly effective at triggering ice nucleation at temperatures below −15.0 °C, with a notable increase in INP concentration within the range of −15.0 to −23.0 °C, which was related to the unique dynamic processes of phytoplankton bloom and growth (Brooks and Thornton, 2018;McCluskey et al, 2017;Thornton et al, 2023;Wilbourn et al, 2020). Our study detected the high concentrations of bio-INPs in the LTR originating from the Japan Sea (Fig.…”
Section: Transport Pathways Of Inpsmentioning
confidence: 99%
“…For example, Wilson et al (2015) found that the biogenic organic materials within the sea surface microlayer could induce droplet freezing in the immersion mode, with a broad freezing-temperature range of −7.0 to −35.0 °C. Laboratory experiments have further revealed that aerosols generated by phytoplankton are particularly effective at triggering ice nucleation at temperatures below −15.0 °C, with a notable increase in INP concentration within the range of −15.0 to −23.0 °C, which was related to the unique dynamic processes of phytoplankton bloom and growth (Brooks and Thornton, 2018;McCluskey et al, 2017;Thornton et al, 2023;Wilbourn et al, 2020). Our study detected the high concentrations of bio-INPs in the LTR originating from the Japan Sea (Fig.…”
Section: Transport Pathways Of Inpsmentioning
confidence: 99%